Remaking Central Europe the League of Nations and the former Habsburg lands - Wheatley, Natasha; Becker, Peter (Professor of Austrian history) (Oxford Oxford University Press, 2020)
Over the last two decades, the "new international order" of 1919 has grown into an expansive new area of research across multiple disciplines. With the League of Nations at its heart, the interwar settlement's innovations in international organizations, international law, and many other areas shaped the world we know today. This book presents the first study of the relationship between this new international order and the new regional order in Central and Eastern Europe after the collapse of the Habsburg empire. An analysis of the co-implication of these two orders is grounded in four key scholarly interventions: understanding the legacies of empire in international organizations; examining regionalism in the work of interwar international institutions; creating an integrated history of the interwar order in Europe; and testing recent claims of the conceptual connection between nationalism and internationalism. With chapters covering international health, international financial oversight, human trafficking, minority rights, scientific networks, technical expertise, passports, commercial treaties, borders and citizenship, and international policing, this book pioneers a regional approach to international order, and explores the origins of today's global governance in the wake of imperial collapse. --
Introduction Central Europe and the new international order Peter Becker and Natasha Wheatley -- Glenda Sluga -- Habsburg histories of internationalism Clemens Pirquet : early twentieth-century scientific networks, the Austrian hunger crisis, and the making of the international food expert Michael Burri -- Reinventing international health in east central Europe : the League of Nations, state sovereignty, and universal health Sara Silverstein -- Polycentric international participation after the first world war : experts from east central Europe in and around the League of Nation's Secretariat Katja Castryck-Naumann -- Austria, the League of Nations, and the birth of multicultural financial control Nathan Marcus -- Hungary and the League of Nations : a forced marriage Zoltán Peterecz -- On the fraught internationalism of intellectual : Alfons Dopsch, Austria, and the League's intellectual cooperation programme Johannes Feichtinger -- Remaking mobility : international conferences and the emergence of the modern passport system Peter Becker -- International commerce in the wake of empire : central European economic integration between national and imperial sovereignty Madeleine Dungy -- Fighting the scourge of international crime : the internationalization of policing and criminal law in interwar Europe David Petruccelli -- Nation, internationalism, and the policies against trafficking in girls and women after the fall of the Habsburg Empire Martina Steer -- The League of Nations and the optants' dispute in the Hungarian borderlands : Romania, Yugoslavia, Czechoslovakia Antal Berkes -- Non-territorial national autonomy in interwar European minority protection and its Habsburg legacies Börries Kuzmany -- Beyond the League of Nations : public debates on international relations in Czechoslovakia during the interwar period Sarah Lemmen -- An epilogue to the making and unmaking of central Europe and global order Patricia Clavin.
Includes bibliographical references and index.
Keywords: 900-1999; Central Europe; History -- 20th century; History